Perancangan Sistem Informasi Pemesanan Pallet Dengan Metode Waterfall - Romli, Ikhsan; Rizki, Rafli Ardian; Antoni, Andi (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The development of technology always rises and then affects many people, especially in the mindset of those who do not tend to use the highest technology. CVs that accept pallet orders require a program to order pallets that can assist in data processing so that they can simplify their work. Therefore, the author tries to do the final project regarding the ordering program for pallets on the CV. Redhead Mandiri now only uses the process with Microsoft Excel. CV. Redhead Mandiri is a trading company that now only concentrates on pallets and only accepts orders from Industri Mulia. Because data processing in this CV still uses Microsoft Excel, which makes it very possible that errors or errors occur when recording data and ordering transactions, and making reports are not too accurate and make the data slow. Many customers, meaning that many transactions will be processed so that the business owner is diverted to use the benefits of computers to meet the needs of data processing and then. The best solution to overcome this problem in CV Redhen Mandiri is a computer program that can be done. All movements are more effective and efficient in the activities of CV.